Porous and Magnetic Molecularly Imprinted Polymers via Pickering High Internal Phase Emulsions Polymerization for Selective Adsorption of λ-Cyhalothrin - Wu, Yunlong; Ma, Yue; Pan, Jianming; Gu, Runxing; Luo, Jialu (Frontiers in Chemistry, 2017)
A novel macroporous magnetic molecularly imprinted polymer (MMIPs) of was prepared by W/O Pickering (high internal phase emulsions) HIPEs polymerization, and then it was adopted as adsorbent for selective adsorption of λ-cyhalothrin (LC). In static conditions, adsorption capacity of LC increased rapidly in the first 60 min and reached to equilibrium in ~2.0 h. Excellent conformity of the second-order model confirmed the chemical nature of the interaction between the LC and imprinted sites. The fitting adsorption isotherm was a Langmuir type, and the maximum monolayer adsorption capacity at 298 K was 404.4 μmol g−1. Thermodynamic parameters suggested the specific adsorption at 298 K was an exothermic, spontaneous, and entropy decreased process. Competitive recognition studies of the MMIPs were performed with diethyl phthalate (DEP) and the structurally similar compound fenvalerate (FL), and the MMIPs, which displayed high selectivity for LC.